KAJIAN AKAD PEMBIAYAAN MURABAHAH TERHADAP PENERAPAN PRINSIP SYARIAH PADA BANK SYARIAH DI INDONESIA - Ani Yunita (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2015)
This research intended to know whether murabahah financing contract on the sharia banking has fullfill to sharia principles in Islamic law provisions. This research is a normative or doctrinal research. This research is the kind of doctrinal or normative legal using approach of law (statute approach) and conseptual approach so it’s using the secondary dates sources such as primary,secondary and tertiary legal materials. Dates was collected with library research and analyzed by deductive logic. According of research result and analysis that the murabahah financing contract on the Sharia Mandiri Banking in Yogyakarta isn’t suitable sharia principles accordance in the Islamic Law because some requirements in the contract implementation hasn’t fullfill to sharia principles so it founded gharar, riba and zhalim. So, this is inline with sharia principles accordance in the Al-Quran, Al-Hadits and Fatwa Council of Sharia National Number 04/DSN-MUI/IV/2000 on Murabahah and also Law Number 21 Of 2008 on Sharia Banking.